PENGARUH SISTEM DOUBLE BLOWER TERHADAP KINERJA PENDINGINAN AC KENDARAAN PENUMPANG - Farid Hidayatulloh; Gatut Rubiono; Ikhwanul Qiram (Virtual of Mechanical Engineering Article, 2022)
Cooling using air conditioning in passenger vehicles is very important for the user's comfort. The study aims to get the effect of double blowers on the cooling performance of passenger vehicles. The research was conducted using laboratory-scale equipment. The wind speed of the blower varied by 3.1; 3.5 and 3.7 m/s. To measure wind speed using a digital anemometer. Cabin room temperature is measured using type K thermocouples for 4 measurement points, namely the left rear passenger seat (point 1), the right rear passenger seat (point 2), then the front passenger seat (point 3), and the driver's position (point 4). Measurement times varied by 5, 10, 15 and 20 minutes. Visualizing airflow using the smoke method and recorded with a camera. In this study showed that the double blower system affects the cooling performance of passenger vehicle air conditioners